1999
DOI: 10.1165/ajrcmb.20.6.3484
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Induced Changes in Bone-Marrow Progenitor and Airway Dendritic Cells in Sensitized Rats

Abstract: Eosinophilic airway inflammation is orchestrated by T-helper (Th)-2 lymphocytes. We have previously demonstrated that dendritic cells (DC) are essential for the presentation of antigen to these Th2 cells leading to airway inflammation. Here, we have examined the presence of DC in the lungs, the kinetics of appearance, and the possible involvement of the bone-marrow progenitor for DC in a rat model of ovalbumin (OVA)-induced airway inflammation. Sensitized rats were exposed to 0, 1, 3, or 7 consecutive daily OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 55 publications
4
61
0
Order By: Relevance
“…Inhalation of allergens results in presentation by local dendritic cells to T cells in environment rich in T H 2 cytokines, promoting an allergic response in the airways [67]. These interactions lead to activation of eosinophils, induction of IgE production, mast cell proliferation, epithelial cell activation, mucus hypersecretion, and smooth muscle proliferation observed in asthma [68].…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of allergens results in presentation by local dendritic cells to T cells in environment rich in T H 2 cytokines, promoting an allergic response in the airways [67]. These interactions lead to activation of eosinophils, induction of IgE production, mast cell proliferation, epithelial cell activation, mucus hypersecretion, and smooth muscle proliferation observed in asthma [68].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that precursor DCs enter the lung where they differentiate into MHC class II ϩ DC (18,19). At present, little is known about the mechanisms that enable DC precursors to migrate from the blood to the lung, either during steadystate turnover (11) or in response to chemotactic gradients initiated by inhaled Ags (32).…”
Section: Discussionmentioning
confidence: 99%
“…Isotypematched Abs served as a control. DC were identified as low-autofluorescence cells, non-T and non-B lymphocytes, and double positive for Ox6 (MHC class II) and Ox62 (DC marker) (24). For characterization of the MHC class II/Ox62 ϩ DC, cells were stained with Abs against CD80, CD86, CD11c, and CD54, and the mean fluorescence intensity (MFI) was measured.…”
Section: Staining Of Leukocyte Subsets and DCmentioning
confidence: 99%